Determinan Pembangunan Manusia Kabupaten/Kota di Provinsi Jawa Tengah - Darwin Hartono (Sosio e-Kons, 2022)
The background of this research is the inequality of human development in regencies/cities in 2008 to 2012. Thus, the purpose of this research is to analyze the factors influencing of human development as well as the role of local governments and private sectors towards human development in regencies/cities. The method of analysis used is Data Panel Regression with Fixed Effect approach using Eviews 6.0 application. The result of this research show that human development influenced by poverty, Gini index, private investment, open unemployment, economic growth, expenditure of education function and expenditure of health function. Private investment, expenditure of education function and expenditure of health function have a positive significant. Poverty, Gini index, open unemployment and economic growth have a negative significant. The role of local government through expenditure of education function is very large. The role of local government through expenditure of health function has not been too immense. The private sector's role through private investment is quite large.